2012
DOI: 10.5402/2012/593876
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Risk Factors of the Burnout Syndrome in Ob/Gyn Physicians from a Reference Public University of Brazil

Abstract: Objective. To identify the risk factors to the development of Burnout Syndrome in Ob/Gyn Brazilian physicians in four dimensions: emotional exhaustion (EE), professional repression (PR), dehumanization (De), and emotional distancing (EmD). Methods. A prospective cross-sectional study was realized with 48 Ob/Gyn physicians (12 lecturers, 12 attending physicians, 12 medical residents, and 12 graduate students) from Department of Obstetrics, São Paulo Federal University (UNIFESP). We used a sociodemographic quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…To verify the presence of the syndrome, four dimensions are considered, two of which (EmD and De) are the equivalent of depersonalization in the Maslach Burnout Inventory (MBI) 14 , 25 . The BSI has been previously applied to a sample of Brazilian physicians and showed, as in our study, changes beyond the average in negative work conditions, EE and De 26 . In this study, adverse work conditions also prevailed over positive ones, indicating that the participants notice more demands than resources in performing their professional activities.…”
Section: Discussionsupporting
confidence: 69%
“…To verify the presence of the syndrome, four dimensions are considered, two of which (EmD and De) are the equivalent of depersonalization in the Maslach Burnout Inventory (MBI) 14 , 25 . The BSI has been previously applied to a sample of Brazilian physicians and showed, as in our study, changes beyond the average in negative work conditions, EE and De 26 . In this study, adverse work conditions also prevailed over positive ones, indicating that the participants notice more demands than resources in performing their professional activities.…”
Section: Discussionsupporting
confidence: 69%
“…The higher reliability of EE compared to DE and PA has been reported by previous studies (30, 53) and for samples from various countries (4). Actually, although instruments capturing burnout have included distinct dimensions [e.g., professional repression, dehumanization, emotional distancing (54, 55); enthusiasm toward the job, indolence, guilt (56)], they tend to maintain the exhaustion dimension (54, 55). Those findings support the original view that EE is the burnout syndrome‘s core dimension (1).…”
Section: Discussionmentioning
confidence: 99%
“…In one study on obstetricians and gynecologists working in a high-stress environment, 15% reported having "hardened" against people's problems; 25% reported being more a "technical personnel" and less a "person" in the workplace, and 33% reported becoming more violent-almost daily-after working for a while. Further results indicate that 25% of doctors feel they should be rough so as not to lose their jobs (Bortoletti et al, 2012).…”
Section: Advanced Level Of Division Of Labor and Specializationmentioning
confidence: 99%